1992
DOI: 10.1007/bf02285085
|View full text |Cite
|
Sign up to set email alerts
|

Predominantβ-adrenoceptor blocking effect of xamoterol averaged over the day in patients with mild to moderate heart failure: insight into the mechanism of its long-term clinical efficacy

Abstract: Xamoterol acts as a beta 1-adrenoceptor agonist at low sympathetic activity and as an antagonist at high activity. Although its long-term efficacy has been proven in patients with mild to moderate heart failure, it remains unclear which effect, agonism or antagonism, accounts for its long-term activity. To clarify the effect of xamoterol on cardiac sympathetic activity in daily life, 24-h R-R interval histograms were obtained during administration of xamoterol 100 mg b.d. for 1 week to 10 patients with mild to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Moreover, the blunted blood flow response may cause compensatory activation of sympathetic nerves even during light exercise such as walking, imposing an additional load on the failing heart. Indeed, it has been reported that the increase in plasma norepinephrine concentration while walking is much greater in patients with chronic heart failure than in normal subjects (24). Thus, as well as improvements of nonspecific vasodilating responses, an improvement in the muscle pump-dependent blood flow response may be a novel therapeutic strategy for chronic heart failure, which allows for an improvement of the quality of life with a cardioprotective effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the blunted blood flow response may cause compensatory activation of sympathetic nerves even during light exercise such as walking, imposing an additional load on the failing heart. Indeed, it has been reported that the increase in plasma norepinephrine concentration while walking is much greater in patients with chronic heart failure than in normal subjects (24). Thus, as well as improvements of nonspecific vasodilating responses, an improvement in the muscle pump-dependent blood flow response may be a novel therapeutic strategy for chronic heart failure, which allows for an improvement of the quality of life with a cardioprotective effect.…”
Section: Discussionmentioning
confidence: 99%
“…The upright bicycle exercise test was performed during a postabsorptive state in the afternoon. In the present study as well as in several previous studies (15,24,32), the pressure in the ankle vein was measured to estimate the venous pressure changes in exercising legs. Before the exercise test, a 22-gauge Teflon needle was inserted into the superficial ankle vein.…”
Section: Subjectsmentioning
confidence: 93%
“…They do not directly controvert the beneficial effects of physical exercise in patients with chronic heart failure because most rehabilitation programmes use a less intense exercise protocol than that used in our study. However, sympathetic activation that may account for exercise induced diastolic dysfunction is inevitable even during submaximal exercise in patients with chronic heart failure 37. Although further studies are needed to assess the optimal amount of exercise in patients with chronic heart failure, our results imply that an adequate interval between exercise episodes is essential to reduce the risk of progression of heart failure during long term exercise training.…”
Section: Discussionmentioning
confidence: 77%
“…It is of note that, although the long-term clinical efficacy of xamoterol has been reported in patients with mild to moderate heart failure [20][21][22], the drug has been demonstrated to worsen the prognosis of patients with severe heart failure [23]. In patients with severe heart failure, xamoterol acts as an antagonist, even at rest, because of increased sympathetic activity [24]. Hence, cardiac decompensation may occur during xamoterol administration to patients with severe heart failure.…”
Section: Discussionmentioning
confidence: 99%